BERMAIN DAN KREATIVITAS DALAM PEMBELAJARAN PENDIDIKAN JASMANI - Yuyun Ari Wibowo (Jurnal Pendidikan Jasmani Indonesia, 2010)
Play is an activity that is done with excitement, satisfaction without compulsion, by the perpetrators. Creativity is a result of human thinking to resolve pressure and problem. This paper wants to reveal the relationship between play, creativity, and teaching physical education. Playing rough to develop muscle and smooth muscle, improve reasoning, and understand the existence of their environment, shaping the imagination, the fantasy, and creativity. Playing any culprit will be able to make do creatively. Actually, everyone would love to play. Playing basically always use physical activity and psychological, so play can be made for learning, especially learning of physical education. Physical education learning enables submitted with the form of play. Physical education learning approach to play will be able to foster creativity for students through games that they do. Keywords: Games, Creativity, Teaching Physical Education